Clinical Characteristics of Noncancer-Related Upper Back Pain on Initiation of Palliative Care in Patients with Incurable Cancer - Hideaki Hasuo; Kiyohiro Sakai (Palliative Medicine Reports, 2021)
Background: Cancer patients experience various types of pain unrelated to their malignancy. However, no previous study has reported the prevalence of noncancer-related pain among patients with incurable cancer. Objective: We aimed to investigate the frequency of noncancer-related upper back pain, the type of noncancer disease, and pain intensity among patients. Design: This is a multicenter cross-sectional survey. Setting/Subjects: Subjects were patients with incurable cancer who underwent initiation of palliative care at two university hospitals in Japan. Measurements: Data for patient characteristics were recorded, and the upper back pain intensity, duration, analgesic use, and opioid drug use with dose were determined. Appropriate statistical tests were also performed. Results: Among the 103 patients with upper back pain, 20 (19.4%) had cancer-related pain, 28 (27.2%) had both cancer- and noncancer-related pain, and 53 (51.5%) had only noncancer-related pain. Myofascial pain was suspected in the 72 (88.9%) participants with noncancer-related pain. The median pain numerical rating scale score was four in the cancer-related pain group and seven in the other two groups (p?=?0.005). Conclusions: A high proportion of outpatients with incurable cancer undergoing palliative care initiation had noncancer-related upper back pain. Severe pain at the initiation of palliative care in patients with incurable cancer may include noncancer-related pain. Trial Registration: UMIN000038371. Registered December 1, 2019.